Cumulative Impacts of Land Cover Change and Dams on the Land–Water Interface of the Tocantins River - Swanson, A. Christine; Bohlman, Stephanie (Frontiers in Environmental Science, 2021)
Riparian vegetation performs important ecosystems services, improving water quality, mitigating erosion, and maintaining regional plant and animal biodiversity. Regular annual flooding maintains riparian forests through an intermediate disturbance regime. In response, seasonally flooded vegetation has developed adaptations for seed dispersal and gas transfer to survive and reproduce while undergoing periods of flooding. In the Amazon, a dam building boom threatens the integrity of riparian vegetation by moving riparian corridors into dry-adapted ecosystems and reducing downstream flooding of riparian areas. Additionally, the region is undergoing intense development pressure resulting in the conversion of native riparian vegetation into agriculture. In this study, we measure how the installation of six large dams on the Tocantins River, coupled with land cover change from native forest and savanna to cattle pasture, has changed the land-water interface of this region. Using land cover data provided by MapBiomas, we quantified land cover change from 1985-2018 and measured changes in the riparian areas of the still free-flowing areas of the Tocantins River, riparian areas surrounding reservoirs, and in-stream vegetation dynamics. We found that deforestation in the riparian areas of the Tocantins River downstream of the dams is occurring at a higher rate than deforestation in the watershed. Additionally, reservoir filling resulted in creating hundreds of square kilometers of new riparian areas, pushing the riparian zone away from forest-dominated ecosystems into savanna-dominated areas. The quantity of in-stream vegetation throughout the study was dynamic and initially increased after damming before declining for the last decade of the study. Changes to native land cover in riparian areas of the Tocantins River threaten the integrity of ecosystem services provided by riparian vegetation and are likely to lead to further degradation of these areas.